2004
DOI: 10.1007/s00403-004-0481-4
|View full text |Cite
|
Sign up to set email alerts
|

Molecular interactions of B-CAM (basal-cell adhesion molecule) and laminin in epithelial skin cancer

Abstract: Molecular events underlying the progression of malignant tumors through the surrounding tissue are largely mediated by membrane-bound adhesion molecules. Basal-cell adhesion molecule (B-CAM), a 90-kDa laminin receptor of the immunoglobulin superfamily, is induced in some epithelial malignancies. Its function in these tumors, however, still remains obscure. We demonstrated that expression of B-CAM is very weak, if detectable at all, in normal epidermis but is strongly induced in both basal cell carcinomas and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 34 publications
1
23
1
Order By: Relevance
“…The Lu/B-CAM antigens are also expressed in epithelial tissues (11,47). This is consistent with the presence of laminin ␣5 in these tissues (48).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The Lu/B-CAM antigens are also expressed in epithelial tissues (11,47). This is consistent with the presence of laminin ␣5 in these tissues (48).…”
Section: Discussionsupporting
confidence: 79%
“…For example, adhesion mediated by integrin ␣4␤1 results in increased T cell migration via a phosphorylation-mediated interaction with paxillin, a signaling adaptor protein (52). Moreover, it has recently been demonstrated that Lu/B-CAM is functionally involved in skin tumor cell binding and migration through the laminin ␣5 containing stroma (47). Since laminin also appears to increase tumor cell adhesion and migration, it will be of interest to further analyze the impact of Lu phosphorylation on these biological events in normal and pathological epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…In complementary experiments, murine 3T3 fibroblasts were chosen as recipients, which show no constitutive expression of B-CAM. As observed recently, human B-CAM was functional in murine cells inasmuch as it conferred laminin-directed adhesion and migration [1,4]. Again, using the pcDNA3.1(-) expression construct, high levels of B-CAM expression were achieved (MFI approximately 300; fig.…”
Section: Resultsmentioning
confidence: 62%
“…We have previously shown that B-CAM is not expressed in normal epidermis, but is strongly induced de novo in epithelial skin tumors, i.e., basal cell carcinomas and squamous cell carcinomas [3]. In these tumors, B-CAM presumably contributes to local progression through enhanced migration on laminin-containing matrices [4]. However, there are several functional features associated with expression of B-CAM which cannot easily be attributed to the known adhesive function as a laminin receptor.…”
Section: Introductionmentioning
confidence: 99%
“…The chromosomal gain of the 454 Kb window within 19q13.31-q13.32 was also more frequently presented in female HCC cases than in male HCC patients in the present study. Cancer-related genes, such as BCL3, BCAM, and RELB (Drewniok et al, 2004;Maldonado et al, 2010;Slovak et al, 2011) are located in this region.…”
Section: Discussionmentioning
confidence: 99%